Proposta e avaliação de um método adaptativo de corte de carga - Silva Júnior, Samuel Souza da (2017)
This work deals with the evaluation of adaptive methods of load shedding. It is understood as adaptive methods, load shedding schemes that are able, through monitoring the state of the network, to estimate the unbalance between the load and the generation of the system and to adapt the amount of load to be rejected. Methods found in the literature to estimate the power deficit, load cut distribution and the considerations assumed during the execution of the load shedding scheme are presented. The considerations presented are used for the development of a new adaptive method. The requirements and challenges in the implementation of a centralized adaptive protection are discussed, especially, in the use of synchronized phasor measurement systems. Finally, the proposed method is evaluated in different IEEE benchmark systems, so that the importance of each presented consideration is illustrated and its applicability in systems of different sizes is tested. The simulation is performed in the time domain, using the power systems analysis toolbox PSAT for Matlab©.